Anticipated Gains: Motherwork, Organizational Brokerage, and Daughter's Occupational Development. Issue 4 (2nd October 2022) - Eyal-Lubling, Roni; Benjamin, Orly
ABSTRACT: Research on mothers' efforts to protect their families from scarcity tends to separate individual action and the organizational context. We propose an intergenerational approach focusing on the convergence between the two, and ask: how are resources, acquired by motherwork vis-à-vis organizations, transferred to daughters to advance their occupational development? Based on 30 interviews with economically marginalized mother-young adult daughter dyads, the findings reveal an intergenerational brokerage of organizational ties, creating a resource for the occupational development of young women. We argue that in the context of poverty, organizational ties are crucial for mothers striving to support their daughters' occupational development.